Clinical associations, biological risk factors and outcomes of cerebral venous sinus thrombosis - Gunes, Hafize Nalan (J Int Med Res, 2016)
OBJECTIVE: Cerebral venous sinus thrombosis (CVST) is a rare cerebrovascular disease affecting young adults. The majority of the patients are female. The aim of this study is to assess the clinical associations, risk factors and outcomes of the patients with CVST. METHODS: The data of 75 patients with CVST admitted to our hospital between 2006 and 2016 were reviewed. Demographic and clinical features and the thrombophilic risk factors of the patients were recorded. The localizations of the thrombi were determined and modified Rankin score at the time of onset and discharge were calculated. RESULTS: The majority of our patients (78.7%) were female. Median age was 35 years (16–76). The most common symptom was headache (86.7%). In 82.6% of our patients, inherited or acquired risk factors for thrombosis were detected. Transverse sinus was the most common site of thrombosis followed by sigmoid and superior sagittal sinuses. Two thirds of the patients had involvement of multiple sinuses. The patients with the involvement of sagittal sinus had better disability at the time of admittance (p = 0.013) while the number of involved sinuses was correlated worse disability (p = 0.015). The neurologic states in the majority of the patients were improved by the end of the hospitalization period (p = 0.001). There was no significant difference in disability score at discharge between men and women (p = 0.080). No patient with CVST died in the hospitalization period. CONCLUSIONS: This study is one of the largest cohort studies on CVST in our region. The results of the study disclosed that CVST had wide range of clinical manifestations and non-specific symptoms at the beginning. For that reason, in especially high risk groups for thrombosis, the diagnosis of CVST should be kept in mind.